(untitled) (Hoboken, New Jersey, 2017)
This book provides comprehensive guidance to help you construct a plan to help workers to retire with confidence. Adopt a framework for DC evaluation and structure. Learn new methodologies for investment choice evaluation. Use the innovative PIMCO Retirement Income Cost Estimate—or PRICE—to help quantify the amount of money a worker needs to create and stay on track to building a real income stream in retirement. Examine methodologies used at major companies in the U.S. and globally.
Keywords: Quản trị tài chính,Financial management